Development of ice hockey in Chengdu (China) - Mingfeng, Y. (Theory and Practice of Physical Culture, 2025)
This article analyzes the development of ice hockey in Chengdu. Chengdu is a strategic hub for the development of the western part of the People's Republic of China and an important gateway connecting China with the Middle East and Europe. The growing popularity of ice hockey in the region is linked to government support for the sport, as well as the development of economic ties with geographical neighbors.